Uma análise sobre a produção, produtividade e colaboração na Ciência da Informação no Brasil entre os anos 2007 a 2009 - Andretta, Pedro Ivo Silveira (2012)
This research comprises some considerations about production, productivity and scientific collaboration related to Information Science in geopolitical regions of Brazil, aiming at identifying their macro-level flow and trends. Reports were generated through identification of Information Science postgraduate programs and professors and collaborators who work on them - those reports were synthesized according to programs and regions, from the year of 2007 to 2009. We can conclude that the Southeast and Northeast regions are responsible for the higher production, productivity and collaboration indicators; we can also infer that the expansion of the relationship among different regions may offer the researchers opportunities to establish new partnerships, and to develop researches on emerging subjects in this scientific area